2023
DOI: 10.3390/ijms24076222
|View full text |Cite
|
Sign up to set email alerts
|

Building Bricks of Integrated Care Pathway for Autism Spectrum Disorder: A Systematic Review

Abstract: An integrated plan within a defined care pathway for the diagnosis, continuative interventions, and periodic redefinition of care of autistic people is essential for better outcomes. Challenges include delivering services across all domains or life stages and effective coordination between health/social care providers and services. Further, in the ‘real world’, service provision varies greatly, and in many settings is significantly weighted towards diagnosis and children’s services rather than treatment and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Fulceri et al’s review [ 5 ] delved into and identified existing care pathways from referral to post-diagnosis management for individuals with autism through strict criteria in published articles. They examined the challenging transition from adolescence to adulthood, finding that what emerges is the need for multidisciplinary care and effective coordination among various healthcare/social service providers.…”
mentioning
confidence: 99%
“…Fulceri et al’s review [ 5 ] delved into and identified existing care pathways from referral to post-diagnosis management for individuals with autism through strict criteria in published articles. They examined the challenging transition from adolescence to adulthood, finding that what emerges is the need for multidisciplinary care and effective coordination among various healthcare/social service providers.…”
mentioning
confidence: 99%